Pasar Modal Syari'ah Dalam Laju Pertumbuhan Ekonomi Di Indonesia - Syahdan, Abdul; Fahreza, Rendi Gustan; Gultom, Fadly Anhar; Ardiansyah, Dimas; Nasution, Yusuf Zibron (Tabayyun : Journal Of Islamic Studies, 2024)
By expanding the investment sector, the capital market can help the Indonesian economy grow faster. The capital market has a major impact on the process of economic progress of a nation. Islamic communities in Indonesia have investment options thanks to the sharia capital market which is based on sharia principles. Investing is one of the muamalah practices recommended by Islam because it can increase a person's productivity and provide benefits to other people. The purpose of writing this article is to find out how the Islamic capital market helps Indonesia's economic growth. This research was conducted using qualitative methods. The results of this research show that a country's Gross Domestic Product (GDP) indicates the country's economic growth level. In 2021, the processing sector will contribute 19.25% of Indonesia's economic development after the COVID-19 epidemic subsides. Market players realize that securities trading can contribute to Indonesia's economic growth by offering relatively high rates of return to investors. Due to different social perspectives, Islamic capital markets have not emerged as a major concern. However, it is estimated that by reaching a wider audience, the number of investors in the Islamic capital market will increase, and possibly contribute to the expansion of the Indonesian economy.